Monitoring of Retinoic Acid Uptake into H9c2 Cells Using Electric-Double-Layer (EDL) Gated Field-Effect Transistors. (24th August 2020) - Tsai, Shu-Yi; Wang, Jen-Hsuan; Chen, Po-Hsuan; Paulose, Akhil K.; Wang, Yu-Lin; Chen, Jung-Chih
Abstract : Fibronectin-immobilized extended gated electric-double-layer field-effect transistors are demonstrated for non-invasively monitoring retinoic acid uptake by H2c9 cell lines. The diffusion of retinoic acid into the cells is electrically measured as the drain current gain based on the change of the voltage drop in culture medium produced by the capacitance change of the cells. Impedance measurement and analysis reveal that the imaginary part dominates the major voltage drop in medium and the sensing characteristics as well. The sensor chip is confirmed to be a capacitive equivalent model and combining with the signal amplification by FETs. This non-invasive cell-based sensor platform enables to monitor the interaction between molecules and cells, which is promising for prospective applications in all kinds of intracellular study and drug screening.